Storytelling in design : defining, designing, and selling multidevice products - Dahlström, Anna, ....- (Beijing : O'Reilly, 2020)
With the wide variety of devices, touch points, and channels in use, your ability to control how people navigate your well-crafted experiences is fading. Yet it's still important to understand where people are in their journey if you're to deliver the right content and interactions atthe right time and on the right device. This practical guide shows you how storytelling can make a powerful difference in product design. Author Anna Dahlström details the many ways you can use storytelling in your projects and throughout your organization. By applying tried-and-tested principles from film and fiction to the context of design and business, you'll learn to create great product experiences. Learn how the anatomy of a great story can make a difference in product design Explore how traditional storytelling principles, tools, and methods relate to key product design aspects Understand how purposeful storytelling helps tell the right story and move people into action Use storytelling principles to tell, sell, and present your work
Keywords: Product design; Productontwikkeling; Storytelling